The Relationship of Work-Life Balance and Quality of Life among Women Employees in Universiti Sultan Zainal Abidin, Malaysia - Fatimah Muliana Tengku Muda, Tengku; Noorul Madihah Syed Husin, Syh; Khatijah Ismail, Siti; Mohd Yusoff, Zurita; Fatimah Salleh, Siti; Mohd Yusof Wan Chik, Wan; Binti Zakaria, Nadiah (International Journal of Psychosocial Rehabilitation, 2020)
Life and work overlap and interact regardless of education level, gender, occupation, or age. A shifting trend in the labor market witnessed a rapid increase of women in the workforce, heightening the awareness of work-life issues. In contrast, conflicts between work and personal life priorities can be a catalyst for a low quality of life. Thus, this study aimed to investigate the relationship between work-life balance and the quality of life among women employees in UniSZA, Malaysia. A quantitative method was employed, whereby data were analyzed using the Structural Equation Modeling (SEM) with the IBM-SPSS-AMOS program version 21.0. Three dimensions of work-life balance were assessed: work interference with personal life, personal life interference with work and personal life, and work/personal life enhancement. The findings revealed that there is a high correlation between work-life balance and the quality of life among women employees in UniSZA, Malaysia.